2006
DOI: 10.2176/nmc.46.581
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion-Weighted Magnetic Resonance Imaging of the Spinal Cord in Cervical Spondylotic Myelopathy

Abstract: Principles of echo shifting with a train of observations was used to perform magnetic susceptibilityweighted magnetic resonance imaging with bolus-tracking in 14 patients with spondylotic myelopathy to assess changes in perfusion parameters of the spinal cord before and after decompression surgery for cervical spondylotic myelopathy. The mean transit time (MTT), bolus arrival time (T0), and time to peak (TTP) were obtained from regions of interest (ROIs) and assessed as the ratio between the spinal cord and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Instead, two studies have investigated spinal cord perfusion in DCM using dynamic susceptibility contrast (DSC) imaging with IV gadolinium, demonstrating that the degree of ischemia and hypoxia correlated with neurological status (mJOA), 109 and that post-operative improvement in perfusion corresponds with neurological recovery. 110 …”
Section: Quantitative Imaging Techniquesmentioning
confidence: 99%
“…Instead, two studies have investigated spinal cord perfusion in DCM using dynamic susceptibility contrast (DSC) imaging with IV gadolinium, demonstrating that the degree of ischemia and hypoxia correlated with neurological status (mJOA), 109 and that post-operative improvement in perfusion corresponds with neurological recovery. 110 …”
Section: Quantitative Imaging Techniquesmentioning
confidence: 99%
“…A recent 3T study, in 22 DSCC patients with or without myelopathy, identified a significant relationship (p < 0.05) of DSC markers with the anteroposterior diameter and mJOA scale and suggested that the degree of ischemia and hypoxia correlates with compression severity and clinical status, respectively [103]. Another 1.5T DSC study, in 14 DCM patients, then showed improvement in the spinal perfusion after surgical decompression [104] and pseudo-continuous arterial spin labeling, which, unlike DSC and DCE, does not require an intravenous contrast agent, revealed secondary alteration of cerebral blood flow perfusion in DCM patients [105].…”
Section: Perfusion Weighted Imagingmentioning
confidence: 97%
“…Chronic DSCC reduces blood flow in spinal arteries and results in chronic SC ischemia in histological and animal models [1,71], which is a vital factor in DCM pathogenesis. While perfusion imaging methods, including dynamic susceptibility contrast (DSC), dynamic contrast-enhanced (DCE), and arterial spin labeling perfusion imaging, are commonly used in brain studies, there have been sparse applications in the SC [103][104][105]. A recent 3T study, in 22 DSCC patients with or without myelopathy, identified a significant relationship (p < 0.05) of DSC markers with the anteroposterior diameter and mJOA scale and suggested that the degree of ischemia and hypoxia correlates with compression severity and clinical status, respectively [103].…”
Section: Perfusion Weighted Imagingmentioning
confidence: 99%
“…A recent 3T study in 22 patients with cervical spondylosis with or without myelopathy identified a relationship between DSC markers and anteroposterior diameter and mJOA scale and suggested that the degree of ischemia and hypoxia correlates with compression severity and clinical status, respectively [124]. Another 1.5T DSC study in 14 DCM patients then showed improvement in the SC perfusion after surgical decompression [125] and pseudo-continuous arterial spin labelling, which, unlike DSC and DCE, does not require intravenous contrast agent, revealed secondary alteration of cerebral blood flow perfusion of DCM patients caused by SC compression [126]. Automatic compression ratio and cross-sectional area estimation outperforms manual raters 66 HC AUC, area under the curve; FA, fractional anisotropy; MD, mean diffusivity; AD, axial diffusivity; RD, radial diffusivity; f1, primary partial volume fraction (anisotropic compartment of Ball-and-Sticks model); d, Ball-and-Sticks model diffusivity; MTR, magnetic transfer ratio; 1 H-MRS, single-voxel magnetic resonance spectroscopy; WM, white matter; GM, gray matter; mJOA, modified Japanese Orthopaedic Association scale; tNAA, total N-acetylaspartate.…”
Section: Perfusion Weighted Imagingmentioning
confidence: 98%